2014
DOI: 10.1371/journal.pone.0089884
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G2 Suppresses Estrogen-Mediated Osteogenesis through Inhibition of Wnt/β-Catenin Signaling

Abstract: Estrogen plays an important role in the maintenance of bone formation, and deficiency in the production of estrogen is directly linked to postmenopausal osteoporosis. To date, the underlying mechanisms of estrogen-mediated osteogenic differentiation are not well understood. In this study, a pluripotent mesenchymal precursor cell line C2C12 was used to induce osteogenic differentiation and subjected to detection of gene expressions or to manipulation of cyclin G2 expressions. C57BL/6 mice were used to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Apart from its critical role in glycolysis, LDHA also facilitates tumour progression, including glioma 39. To verify an interaction between cyclin G2 and LDHA, cyclin G2 was overexpressed in U87 and U251 as previous described 40. Co-immunoprecipitation confirmed that cyclin G2 formed a complex with LDHA (Figure 4b).…”
Section: Resultssupporting
confidence: 67%
“…Apart from its critical role in glycolysis, LDHA also facilitates tumour progression, including glioma 39. To verify an interaction between cyclin G2 and LDHA, cyclin G2 was overexpressed in U87 and U251 as previous described 40. Co-immunoprecipitation confirmed that cyclin G2 formed a complex with LDHA (Figure 4b).…”
Section: Resultssupporting
confidence: 67%
“…Estrogen may induce osteoblast differentiation in bone formation by binding the estrogen receptor through the upregulation of PACE4 expression [51], and it also has an anabolic effect on the function of osteoblasts [52]. Estrogen serves different biological functions in the regulation of osteogenic differentiation with involvement of the Wnt/β-catenin signaling pathway [53]. Estrogen loss may also influence the immune system through upregulation of T and B cells [54].…”
Section: Estrogen Deficiency Induced the Expression Of Different Cmentioning
confidence: 99%
“…Recent studies suggested that cyclin G2 could inhibit canonical Wnt signalling in bone metabolism and epithelial ovarian cancer [ 13 , 14 ]. In this study, overexpression of cyclin G2 in HMC cells resulted in the negative regulation of proteins involved in canonical Wnt signalling and suppressed the high-glucose–induced upregulation of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have demonstrated that cyclin G2 has potent tumour-suppressive activity in epithelial ovarian cancer by inhibiting EMT through the attenuation of Wnt signalling [ 13 ]. The results from our preliminary studies suggested that cyclin G2 ( CCNG2 ) could inhibit canonical Wnt signalling and regulate bone metabolism [ 14 ]. However, no evidence has shown whether cyclin G2 specifically functions in the occurrence and development of DN via this pathway.…”
Section: Introductionmentioning
confidence: 99%